2003
DOI: 10.1556/aalim.32.2003.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Recognition experiments of the vintage year 1997 hot and red paprika (Capsicum annuum) varieties grown in Kalocsa

Abstract: Comparison of Hungarian ground red paprika volatiles of known origin (identical to cultivated varieties grown in Kalocsa, Hungary) and provenance has been performed following simultaneous distillationextraction sample preparation. After polar phase capillary gas-chromatography, mass spectrometric identification of as many compounds as possible was carried out to precisely describe the aroma profile of the cultivars. For conceptualizing the results a data evaluation and interpretation method has been elaborated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
4
0
6
Order By: Relevance
“…A double normalization method was previously developed and has been routinely applied to eliminate the distortion effects of the gas chromatographic measuring process (Kocsis et al, 2002(Kocsis et al, , 2003Amtmann, 2005, 2006). This process gives rise to transformed (normalized) TICs, called relative aromagrams (or aromaspectra to emphasize the similarity of the records to mass spectra), which always match if good similarity or identity exists among samples, and differ if the samples are not identical.…”
Section: Ms Identification Of the Flower And Honey Fragrance Constitumentioning
confidence: 99%
“…A double normalization method was previously developed and has been routinely applied to eliminate the distortion effects of the gas chromatographic measuring process (Kocsis et al, 2002(Kocsis et al, , 2003Amtmann, 2005, 2006). This process gives rise to transformed (normalized) TICs, called relative aromagrams (or aromaspectra to emphasize the similarity of the records to mass spectra), which always match if good similarity or identity exists among samples, and differ if the samples are not identical.…”
Section: Ms Identification Of the Flower And Honey Fragrance Constitumentioning
confidence: 99%
“…Flavour profile of Chilli pepper from various parts of the world has been reported (Wu et al, 1996;Guadayol et al, 1997;Sekiwa-Iijima et al, 2002;Kocsis et al, 2003;Conforti et al, 2007), but few studies have been reported on the volatile composition of chinese chilli pepper. This report describes the changes in volatile organic components (VOCs) during the processing of Ripening, the first step for investigation of aroma origins.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it reports on the experience gathered in an 8-year span of scent and fragrance recognition investigation conducted in the field of Hungarian food product specialities (e.g., Muscat ottonel wine, Kov! acs et al, 1999; Red paprika spice powder, Kocsis et al, 2002;Kocsis et al, 2003). These products are called by a collective noun ''Hungarics''.…”
Section: Introductionmentioning
confidence: 99%